cffdrs: an R package for the Canadian Forest Fire Danger Rating System - Wang, Xianli; Wotton, B. Mike; Cantin, Alan S.; Parisien, Marc-André; Anderson, Kerry; Moore, Brett; Flannigan, Mike D. (Ecological processes, 2017)
Introduction The Canadian Forest Fire Danger Rating System (CFFDRS) is a globally known wildland fire risk assessment system, and two major components, the fire weather index system and the fire behavior prediction system, have been extensively used both nationally and internationally to aid operational wildland fire decision making. Methods In this paper, we present an overview of an R package cffdrs, which is developed to calculate components of the CFFDRS, and highlight some of its functionality. In particular, we demonstrate how these functions could be used for large data analysis. Results and Discussion With this cffdrs package, we provide a portal for not only a collection of R functions dealing with all available components in CFFDRS but also a platform for various additional developments that are useful for the understanding of fire occurrence and behavior. This is the first time that all relevant CFFDRS methods are incorporated into the same platform, which can be accessed by both the management and research communities.